Аналіз етапів створення ігрових додатків - Крупка, Є. А. (ХНУРЕ, 2025)
This research focuses on the development of gaming applications, emphasizing design, gameplay mechanics, and user interaction. It explores modern approaches, tools, and technologies used in video game creation, providing a deep er understanding of this field. Special attention is given to gameplay mechanics, visual design, and user interface. By combining theoretical analysis with practical implementation, the research aims to offer valuable recommendations for developers working on games without a narrative component. The primary goal is to expand the possibilities of the gaming industry, foster creativity, and deliver an engaging experience for players.
Keywords: створення ігрових додатків; gaming applications